Traumatic dental injuries to the anterior teeth among 12-year and 15-year-old schoolchildren of urban and rural areas of Bhopal District, Central India: A prevalence study - Vijayta Sharva; Venugopal Reddy; Ajay Bhambal; Rohit Agrawal; Manoj Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Traumatic dental injuries (TDIs) are one such condition that can occur at any age, but the trauma to children's teeth occurs quite frequently. TDIs involving the anterior teeth may not only lead to restriction in biting, phonetics, and esthetics but also have an impact on a child's personality and quality of life. The objective of this study was to assess the prevalence of the TDIs of the permanent anterior teeth among 12-year- and 15-year-old schoolchildren of urban and rural areas of Bhopal district, Central India. Materials and Methods: The descriptive cross-sectional survey was carried on 1100 schoolchildren. For the selection of schools, a three-stage sampling procedure was adopted. A specially prepared and pretested pro forma designed for collecting all the required and relevant general information and clinical findings. The pro forma including the demographic data and questions regarding history of injury to detect the cause, place, duration of trauma to anterior teeth as well as those seeking the treatment for concerned problem was recorded. For clinical examination of TDI to anterior permanent teeth, the World Health Organization (International Classification of Diseases to Dentistry and Stomatology) classification of tooth fracture was used. SPSS version 20 was used for the statistical analysis. The Chi-square test used for categorical data. P < 0.05 was considered statistically significant. Results: The overall prevalence rate of TDIs to permanent incisor teeth was 12.8%. The prevalence of TDI was higher in rural areas compared to urban areas. The major cause of TDI was sports activities. Conclusion: This indicates the need for community health activities and awareness program.